In Vitro Sensitivity Testing of Acanthamoeba Clinical Isolates from Patients with Keratitis against Polyhexamethylene biguanide (PHMB) and Chlorhexidine - Abdullah, NS; Abd Ghani, MK; Nordin, A; Suboh, Y; Ab Rahim, N; Ahmad, N (Univ Kebangsaan Malaysia, 2024)
Acanthamoeba keratitis is a serious infection of the eye which can result in permanent visual impairment. Therefore this study was performed to evaluate the effectiveness of antimicrobial agents on three Acanthamoeba clinical isolates (Hs6, HKL 95 and HTH 73). Antimicrobial agents used in this study were polyhexamethylene biguanide (PHMB) and chlorhexidine and both were serially diluted. Cyst suspensions from all three strains were tested against the antimicrobial agents, respectively. After 48 h of incubation at 37 degrees C, the suspension was filtered and the filter membrane was placed onto non-nutrient agar plate lawned with heat-killed Escherichia coli. The plates were examined daily under the inverted microscope until day 14 but were negative for Acanthamoeba trophozoites. The presence of trophozoites indicated ineffectiveness of the antimicrobial agents. Both antimicrobial agents used were found to be effective against Acanthamoeba cysts for all the strains tested. PHMB gave minimum cysticidal concentration (MCC) mean value of 4.232 mu g/mL and chlorhexidine showed MCC Mean value of 3.906 mu g/mL. So, from this study, it can be concluded that PHMB and chlorhexidine were effective in killing the tested Acanthamoeba cysts.